The Influence of Chromebooks on Students' Critical Reasoning Skills in Science Learning in Elementary Schools - Noriyana, Dita Kharisma; Kuswandi, Iwan; Misbahudholam AR, Muhammad (SAINTIS Publishing, 2024)
In this study, the problems found were the less-than-optimal use of technology-based media in schools, the low critical reasoning ability of students in science learning, and whether this Chrome book can improve students' critical reasoning. This study discusses how the influence of Chrome book media on students' essential abilities of reasoning in science learning. This study uses a quantitative approach with a pre-experimental design of the one-group pretest-posttest design. This study aims to test the effect of using Chromebook media on students' critical reasoning abilities in Elementary Schools. This study focuses on science learning with the material Energy Changes. The population in this study were all fourth-grade students of SD Negeri Kalianget Barat III in the 2024 academic year, as many as ten people. The design taken from this study is a group pretest-posttest design. Based on the calculation of the t-test, tcount = 13.4715 and ttable = 2.262157 were obtained. Thus, count ttable, then the hypothesis proposed is H1 =